2000
DOI: 10.1046/j.1523-1739.2000.98130.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of Ambient Ultraviolet‐B Radiation on Two Sympatric Species of Australian Frogs

Abstract: Declines have been observed in a number of Australian frog species, many of these at high elevations. Alpine regions in Australia are likely to be particularly subject to increases in ultraviolet‐B radiation ( UV‐B, 280–320 nm) because UV‐B levels increase with elevation and because anthropogenic depletion of ozone has been particularly severe in the southern hemisphere. We compared survivorship of embryos and tadpoles of a declining species of frog, Litoria verreauxii alpina, with those of a sympatric nondecl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
52
1
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 44 publications
0
52
1
1
Order By: Relevance
“…Briefly, field and laboratory studies have shown that exposure to UVR can reduce survival, reduce growth, slow the rate of development, induce developmental malformations and abnormalities, reduce locomotor performance, and cause changes in metabolic rate and behaviour (Table 1). Such lethal and sublethal UVR effects have been observed in the embryos, larvae, metamorphs and adults of Limnodynastes peronii Artificial lamps [147] Lithobates sylvaticus Artificial lamps [93] Litoria aurea Ambient sunlight [177] Pseudacris cadaverina Ambient sunlight [179] Rana aurora Ambient sunlight plus artificial lamps [96] Rana cascadae Ambient sunlight [100] Taricha torosa Ambient sunlight [179] Reduced larval survival Ambystoma laterale Ambient sunlight plus artificial lamps [181] Ambystoma macrodactylum Artificial lamps [78,182] Ambystoma maculatum Ambient sunlight plus artificial lamps [181] Anaxyrus americanus Ambient sunlight plus artificial lamps [181] Artificial lamps [93] Bufo bufo Ambient sunlight [180,183] Crinia signifera Ambient sunlight [114] Hyla versicolor Ambient sunlight plus artificial lamps [181] Artificial lamps [93] Hypsiboas pulchellus Artificial lamps [69] Ichthyosaura alpestris Ambient sunlight [81] Artificial lamps [81] Limnodynastes peronii Artificial lamps [62,65] Lithobates clamitans Ambient sunlight [184] Ambient sunlight plus artificial lamps [181] Artificial lamps [93] Lithobates pipiens Ambient sunlight [184][185][186] Artificial lamps [58] Lithobates septentrionalis Ambient sunlight [184] Lithobates sylvaticus Ambient sunlight [188] Ambient sunlight plus artificial lamps …”
Section: Effects Of Uvr On Amphibiansmentioning
confidence: 99%
See 3 more Smart Citations
“…Briefly, field and laboratory studies have shown that exposure to UVR can reduce survival, reduce growth, slow the rate of development, induce developmental malformations and abnormalities, reduce locomotor performance, and cause changes in metabolic rate and behaviour (Table 1). Such lethal and sublethal UVR effects have been observed in the embryos, larvae, metamorphs and adults of Limnodynastes peronii Artificial lamps [147] Lithobates sylvaticus Artificial lamps [93] Litoria aurea Ambient sunlight [177] Pseudacris cadaverina Ambient sunlight [179] Rana aurora Ambient sunlight plus artificial lamps [96] Rana cascadae Ambient sunlight [100] Taricha torosa Ambient sunlight [179] Reduced larval survival Ambystoma laterale Ambient sunlight plus artificial lamps [181] Ambystoma macrodactylum Artificial lamps [78,182] Ambystoma maculatum Ambient sunlight plus artificial lamps [181] Anaxyrus americanus Ambient sunlight plus artificial lamps [181] Artificial lamps [93] Bufo bufo Ambient sunlight [180,183] Crinia signifera Ambient sunlight [114] Hyla versicolor Ambient sunlight plus artificial lamps [181] Artificial lamps [93] Hypsiboas pulchellus Artificial lamps [69] Ichthyosaura alpestris Ambient sunlight [81] Artificial lamps [81] Limnodynastes peronii Artificial lamps [62,65] Lithobates clamitans Ambient sunlight [184] Ambient sunlight plus artificial lamps [181] Artificial lamps [93] Lithobates pipiens Ambient sunlight [184][185][186] Artificial lamps [58] Lithobates septentrionalis Ambient sunlight [184] Lithobates sylvaticus Ambient sunlight [188] Ambient sunlight plus artificial lamps …”
Section: Effects Of Uvr On Amphibiansmentioning
confidence: 99%
“…However, lower temperatures have also been found to enhance the negative effects of UVR independent of exposure duration. Using a fixed exposure duration, Broomhall et al [114] found that the embryos and tadpoles of the alpine tree frog Litoria verreauxii and brown froglet Crinia signifera suffered greater mortality when exposed to UVR at higher elevations where temperatures were cooler. However, because temperature was confounded with elevation, Broomhall et al [114] could not attribute the greater effect of UVR at higher elevations to cooler temperatures specifically.…”
Section: Uvr and Abiotic Factors Temperaturementioning
confidence: 99%
See 2 more Smart Citations
“…The role of UV-B in amphibian physiology is less clear (Gehrmann 1994). Studies of the effect of ultraviolet light on amphibians have emphasized its deleterious effects on eggs and embryos (e.g., Blaustein and Belden 2003;Blaustein et al 1997;Broomhall et al 2000; but see also Licht and Grant 1997 for a contrasting opinion); however, the behavior of some species of frogs exposes them to direct solar radiation for hours at a time (Brust and Preest 1988;Lillywhite 1970;Seymour 1972). Fluorescent bulbs with high UV-B output had no apparent ill effects on the growth of juvenile Wyoming toads (Bufo [ Anaxyus ] baxteri) (R.K. Browne, Perth Zoo, South Perth, Western Australia, personal communication, 2006), but larval salamanders (Ambystoma macrodactylum and Ambystoma gracile) that were exposed to UV-B grew more slowly than individuals that received only full-spectrum illumination (Belden and Blaustein 2002).…”
mentioning
confidence: 99%